Switzerland : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
This paper reviews the trade-offs in Switzerland, focusing on challenges for fiscal policy coordination. It reviews the benefits and costs of a highly decentralized government, describes the Swiss institutional architecture, and analyzes Switzerland's fiscal performance. It also discusses the specific policy challenges related to population aging, reviews the Swiss National Bank works on government financial assets and liabilities, describes the Swiss, Dutch, and the U.K. pension systems, respectively, on the regulation and supervision of the occupational pension pillar, recent reforms, and policy implications.